Organic-inorganic hybrid material for antifouling, preparation method, light-cured antifouling material and product
By performing a ring-opening addition reaction between epoxy polyhedral oligomeric silsesquioxane and amino or carboxyl perfluoropolyether, a POSS hybrid material with PDMS or PFPE linkages is formed, which solves the problem of high surface energy and lack of antifouling properties of epoxy polyhedral oligomeric silsesquioxane coatings. This results in a coating with high thermal stability, wear resistance, and antifouling properties, suitable for outdoor optical devices and medical devices.
Patent Information
- Application Number
- CN202511819191.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-01-27
AI Technical Summary
Existing epoxy polyhedral oligomeric silsesquioxane coatings have high surface energy but lack antifouling properties, making it difficult to meet the antifouling requirements of outdoor optical devices, medical devices, and other scenarios.
POSS hybrid materials with PDMS or PFPE linkages are formed by ring-opening addition reactions of epoxy polyhedral oligomeric silsesquioxanes with amino-containing polydimethylsiloxanes or carboxyl-containing perfluoropolyethers. The chemical bonding is used to achieve synergistic performance, forming a molecular structure with a rigid core and flexible antifouling segments.
It achieves high thermal stability, wear resistance and anti-fouling properties, making it suitable for outdoor optical devices, medical devices and other scenarios, and solving the defects of traditional coatings that have high surface energy and no anti-fouling properties.
Smart Images

Figure CN121405948A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of organic-inorganic hybrid materials technology, and in particular to an organic-inorganic hybrid material for antifouling, a preparation method, a photocurable antifouling material and product. Background Technology
[0002] Epoxy-based polyhedral oligomeric silsesquioxanes (such as glycidyl etheroxypropyl POSS and epoxycyclohexylethyl POSS) are a class of promising organic-inorganic hybrid materials. Their molecular structure is based on an inorganic cage-like framework composed of silicon-oxygen bonds, surrounded by multiple organic epoxy groups. This structure endows the material with excellent thermal stability and structural rigidity. The outer epoxy groups can be cured and cross-linked through cationic or free radical polymerization initiated by ultraviolet (UV) light, forming a transparent three-dimensional network coating. Due to its high hardness, wear resistance, and transparency, this coating shows potential application value in fields such as optical device protection and wear-resistant coatings. However, pure epoxy-based POSS photocurable coatings have significant limitations: their surface energy is relatively high, lacking antifouling properties (such as anti-adhesion, anti-graffiti, and easy-to-clean properties), making it difficult to meet the requirements of self-cleaning or anti-biofouling in outdoor optical devices, medical devices, and marine applications, greatly limiting the expansion of its application scope. Summary of the Invention
[0003] One of the purposes of this application is to provide an organic-inorganic hybrid material for antifouling, which overcomes the shortcomings of the prior art and combines the high thermal stability and structural rigidity of epoxy polyhedral oligomeric silsesquioxane with the excellent low surface energy antifouling properties of amino-containing polydimethylsiloxane or carboxyl-containing perfluoropolyether, effectively overcoming the defect of pure epoxy polyhedral oligomeric silsesquioxane coatings having no antifouling properties.
[0004] The second objective of this application is to provide a method for preparing organic-inorganic hybrid materials.
[0005] The third objective of this application is to provide a photocurable antifouling material, which is prepared by the above-mentioned organic-inorganic hybrid material or the method for preparing organic-inorganic hybrid materials.
[0006] The fourth objective of this application is to provide an article comprising a coating formed by photocuring the aforementioned photocurable antifouling material.
[0007] One of the objectives of this application is to achieve the following technical solution:
[0008] An organic-inorganic hybrid material for antifouling is provided, wherein the organic-inorganic hybrid material is prepared by a ring-opening addition reaction of the epoxy group of an epoxy polyhedral oligomeric silsesquioxane with an amino group or a perfluoropolyether with a carboxyl group.
[0009] In some embodiments, the epoxy polyhedral oligomeric silsesquioxane is selected from at least one of glycidyl etheroxypropyl cage polysilsesquioxane and epoxycyclohexylethyl cage polysilsesquioxane.
[0010] In some embodiments, the polydimethylsiloxane has a number-average molecular weight of 500 to 10000 g / mol and is selected from any one of mono-amino-terminated polydimethylsiloxane and di-amino-terminated polydimethylsiloxane; the perfluoropolyether has a number-average molecular weight of 500 to 5000 g / mol and is selected from any one of mono-carboxyl-terminated perfluoropolyether and di-carboxyl-terminated perfluoropolyether.
[0011] In some embodiments, the number of polydimethylsiloxanes or perfluoropolyethers grafted onto each of the epoxy polyhedral oligomeric silsesquioxanes is 1 to 8.
[0012] The beneficial effects of an organic-inorganic hybrid material for antifouling proposed in this application are as follows:
[0013] This application achieves synergistic performance enhancement through the ring-opening addition reaction of epoxy groups in epoxy polyhedral oligomeric silsesquioxanes (POSS) with amino-containing polydimethylsiloxanes (PDMS) or carboxyl-containing perfluoropolyethers (PFPE). The inorganic cage-like framework of epoxy POSS, composed of high-bond-energy Si-O bonds, imparts high thermal stability and structural rigidity to the material. The Si-O backbone and side chain methyl (-CH3) groups of PDMS, and the CF bonds of PFPE, are low-surface-energy groups, significantly reducing the surface energy of the material. PDMS / PFPE segments are covalently grafted onto the POSS cage-like framework, retaining the inorganic advantages of POSS while introducing low-surface-energy organic segments, forming a molecular structure with a rigid core and flexible antifouling segments. This application overcomes the shortcomings of pure epoxy POSS coatings, which have high surface energy and lack antifouling properties, and can be used to prepare coatings with high thermal stability, wear resistance, and antifouling properties, suitable for outdoor optical devices, medical devices, and other applications.
[0014] The second objective of this application is achieved through the following technical solution:
[0015] A method for preparing an organic-inorganic hybrid material for antifouling is provided, comprising the following steps:
[0016] S1. Under inert gas protection and anhydrous conditions, epoxy polyhedral oligomeric silsesquioxane and catalyst are dissolved in an organic solvent, and then polydimethylsiloxane or perfluoropolyether dissolved in the organic solvent is added and mixed to obtain the composition to be reacted.
[0017] S2. Stir the composition to be reacted at 50°C to 120°C for 4 to 48 hours to allow the epoxy group to undergo a ring-opening grafting reaction with the amino or carboxyl group;
[0018] S3. After the reaction is completed, the reaction product is separated and purified to obtain the organic-inorganic hybrid material.
[0019] In some embodiments, when the composition to be reacted contains polydimethylsiloxane, the catalyst is selected from at least one of boron trifluoride diethyl ether and triethylborane; when the composition to be reacted contains perfluoropolyether, the catalyst is selected from at least one of 4-dimethylaminopyridine and triethylamine.
[0020] In some embodiments, the organic solvent is selected from at least one of toluene, tetrahydrofuran, and N,N-dimethylformamide; in step S1, if the composition to be reacted contains perfluoropolyether, a dehydrating agent is also added to the organic solvent, wherein the dehydrating agent is N,N-dicyclohexylcarbodiimide.
[0021] The beneficial effects of the method for preparing an organic-inorganic hybrid material for antifouling proposed in this application are as follows:
[0022] This application achieves efficient production of structurally stable and highly pure hybrid materials through targeted catalyst selection and controllable condition design. Specific catalysts are selected for different systems. The reaction of PDMS with epoxy polyhedral oligomeric silsesquioxane (POSS) utilizes boron trifluoride diethyl ether / triethylborane, a cationic catalyst capable of activating epoxy groups. The reaction of PFPE with POSS uses DMAP / triethylamine, a basic catalyst capable of catalyzing carboxyl-epoxy esterification. Furthermore, DCC dehydrating agent is added to the PFPE system to further suppress water byproducts and improve product purity. The dissolution, mixing, reaction, and separation purification processes involved in this preparation method are simple and require no complex equipment.
[0023] The third objective of this application is achieved through the following technical solution:
[0024] A photocurable antifouling material is provided, comprising the above-mentioned organic-inorganic hybrid material and photoinitiator.
[0025] In some embodiments, the photoinitiator is selected from at least one of cationic photoinitiators and free radical photoinitiators, and its amount is 0.5% to 5% of the mass of the organic-inorganic hybrid material.
[0026] The beneficial effects of the photocurable antifouling material of this application are as follows:
[0027] The photocurable antifouling material of this application combines the advantages of hybrid materials with photocuring technology, and has the characteristics of rapid prototyping and multifunctionality. The photoinitiator generates active species under UV irradiation, which triggers the cross-linking of the remaining epoxy groups of the hybrid material and rapidly forms a three-dimensional network coating. At the same time, the antifouling property of the coating comes from the low surface energy segments of PDMS / PFPE, while the wear resistance comes from the POSS skeleton, and the transparency comes from the good intermolecular compatibility and no obvious phase separation.
[0028] The fourth objective of this application is achieved through the following technical solution:
[0029] An article is provided, the surface of which is coated with a coating formed by photocuring the aforementioned photocurable antifouling material.
[0030] The beneficial effects of one of the articles of this application:
[0031] The product of this application significantly improves surface performance and service life by coating a light-cured coating. The epoxy polyhedral oligomeric silsesquioxane skeleton in the coating can enhance adhesion to the substrate through chemical bonding and physical anchoring. The PDMS / PFPE flexible molecular brush in the coating is anchored to the POSS rigid network through chemical bonds, forming a dynamic liquid-like low surface energy layer that effectively repels water, oil and biological contaminants. The POSS inorganic cage skeleton constructs a three-dimensional cross-linked network to provide rigid support for the coating. The chemical grafting structure avoids the decrease in mechanical properties caused by physical blending, effectively improving durability, antifouling and wear resistance, and reducing the use of cleaning agents and the frequency of product replacement. Attached Figure Description
[0032] The above and other objects, features and advantages of this application will become more apparent from the more detailed description of exemplary embodiments thereof in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments thereof.
[0033] Figure 1 This is a schematic diagram illustrating the synthetic route of epoxy polyhedral oligomeric silsesquioxane and polydimethylsiloxane as shown in the embodiments of this application;
[0034] Figure 2 This is a schematic diagram illustrating the synthetic route of epoxy polyhedral oligomeric silsesquioxane and perfluoropolyether shown in the embodiments of this application. Detailed Implementation
[0035] Preferred embodiments of the present application will now be described in more detail with reference to the accompanying drawings. While preferred embodiments of the present application are shown in the drawings, it should be understood that the present application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0036] In existing technologies, such as smartphone camera lenses, outdoor photovoltaic module covers, and automotive LiDAR windows, it is necessary to simultaneously meet the requirements of high transparency, high hardness, and stain resistance. Although traditional pure epoxy POSS photocured coatings achieve a hardness of 9H and a light transmittance of 95.1%, their surface is hydrophilic, making them prone to staining and difficult to clean. While physically blended PDMS / POSS coatings improve stain resistance, phase separation leads to a decrease in transparency to 81.3% and a hardness of only 5H, failing to achieve a balance between performance and resistance.
[0037] Applications such as endoscopic catheters, surgical instrument surfaces, and dental restorative materials need to meet the requirements of biocontamination resistance, abrasion resistance, and biocompatibility. In traditional physically blended antifouling coatings, the PDMS / PFPE segments lack chemical bond anchoring, resulting in an antifouling retention rate of only 86.7% after friction. Furthermore, insufficient hardness leads to coating wear, increasing the risk of cross-infection.
[0038] Applications such as ship hulls, marine monitoring buoys, and underwater sensors need to meet requirements for preventing marine organism adhesion, resisting seawater corrosion, and being abrasion resistant. Traditional antifouling coatings either rely on toxic substances or are physically blended with PFPE, but the coatings are prone to peeling and have poor antifouling durability.
[0039] To address the aforementioned pain points, this application provides an organic-inorganic hybrid material that can be used for photocuring and antifouling. It uses epoxy polyhedral oligomeric silsesquioxane (POSS) as its core, and forms a POSS hybrid material with PDMS or PFPE linkages (i.e., PDMS-g-POSS or PFPE-g-POSS) by ring-opening addition reaction between the epoxy groups of the epoxy polyhedral oligomeric silsesquioxane and polydimethylsiloxane (PDMS) with amino reactive groups or perfluoropolyether (PFPE) with carboxyl reactive groups. In this application, PDMS-g-POSS or PFPE-g-POSS achieves synergistic performance through chemical bonding rather than physical blending. The flexible PDMS / PFPE chains are chemically anchored to the rigid POSS core via a ring-opening reaction, avoiding phase separation caused by physical blending and ensuring coating transparency and mechanical properties. Simultaneously, the POSS core retains epoxy groups, forming a three-dimensional rigid network after photocuring, providing the coating with high hardness and wear resistance. Furthermore, the PDMS / PFPE segments form a dynamic molecular brush, providing excellent antifouling properties. This is particularly suitable for optical, medical, and marine applications, overcoming the bottleneck of the trade-off between hardness and antifouling properties, and providing core material support for high-performance coatings in multiple fields.
[0040] In one embodiment of the invention, please refer to Figure 1 and Figure 2This application provides an organic-inorganic hybrid material for antifouling, which is prepared by a ring-opening addition reaction of the epoxy group of an epoxy polyhedral oligomeric silsesquioxane with an amino group or a perfluoropolyether with a carboxyl group.
[0041] Specifically, the ring-opening addition reaction of epoxy polyhedral oligomeric silsesquioxanes can be divided into two directional pathways based on the type of flexible chain end groups: when the flexible chain is a polydimethylsiloxane (PDMS) with amino groups, Lewis acids (such as boron trifluoride diethyl ether) are used as catalysts, and ring-opening grafting is achieved through the nucleophilic attack of the amino group on the epoxy group; when the flexible chain is a perfluoropolyether (PFPE) with carboxyl groups, tertiary amine catalysts are used in combination with dehydrating agents, and grafting is achieved through the esterification ring-opening reaction of the carboxyl group and the epoxy group. This chemical bond grafting method solves the phase separation problem caused by physical blending at the molecular level, ensuring the structural uniformity of the hybrid material.
[0042] Furthermore, the epoxy polyhedral oligomeric silsesquioxane is selected from at least one of glycidyl etheroxypropyl cage-like polysilsesquioxane and epoxycyclohexylethyl cage-like polysilsesquioxane.
[0043] Specifically, the glycidyl etheroxypropyl cage-like polysilsesquioxane (POSS) exhibits high epoxy group reactivity, making it suitable for rapid grafting with amino PDMS and producing products with excellent transparency; the epoxy cyclohexyl ethyl cage-like polysilsesquioxane (POSS) demonstrates better heat resistance, making it suitable for preparing high-temperature resistant and antifouling coatings. Both POSSes can be used individually or in combination to meet the needs of different application scenarios.
[0044] Furthermore, the polydimethylsiloxane has a number average molecular weight of 500–10000 g / mol and is selected from any one of mono-amino-terminated polydimethylsiloxane and di-amino-terminated polydimethylsiloxane; the perfluoropolyether has a number average molecular weight of 500–5000 g / mol and is selected from any one of mono-carboxyl-terminated perfluoropolyether and di-carboxyl-terminated perfluoropolyether.
[0045] Specifically, the number-average molecular weight of polydimethylsiloxane is preferably 500–2000 g / mol, within which the balance between coating hardness and antifouling properties after grafting is optimal. For higher antifouling properties, PDMS with a number-average molecular weight of 5000–10000 g / mol can be selected, but the coating hardness will decrease slightly. The number-average molecular weight of the perfluoropolyether is preferably 1500–3000 g / mol, within which hydrophobicity and compatibility are balanced. Single-terminated amino PDMS avoids excessive crosslinking during grafting, while double-terminated amino PDMS can increase grafting density. Single-terminated carboxyl PFPE is suitable for low grafting density applications, while double-terminated carboxyl PFPE is suitable for high grafting density requirements.
[0046] Furthermore, the number of polydimethylsiloxanes or perfluoropolyethers grafted onto each of the epoxy polyhedral oligomeric silsesquioxanes is 1 to 8.
[0047] Specifically, the preferred number of grafts is 2 to 4. When the number of grafts is 1 to 2, there are more residual epoxy groups in POSS, resulting in a high crosslinking density after photocuring and a coating hardness of 8H or higher. When the number of grafts is 3 to 4, the proportion of flexible chains increases, and the antifouling performance is significantly improved. If the number of grafts exceeds 5, there are insufficient residual epoxy groups, the crosslinking density decreases, and the coating hardness drops to below 7H.
[0048] In another embodiment of this application, a method for preparing an organic-inorganic hybrid material for antifouling is provided, comprising the following steps:
[0049] S1. Under inert gas protection and anhydrous conditions, epoxy polyhedral oligomeric silsesquioxane and catalyst are dissolved in an organic solvent, and then polydimethylsiloxane or perfluoropolyether dissolved in the organic solvent is added and mixed to obtain the composition to be reacted.
[0050] S2. Stir the composition to be reacted at 50°C to 120°C for 4 to 48 hours to allow the epoxy group to undergo a ring-opening grafting reaction with the amino or carboxyl group;
[0051] S3. After the reaction is completed, the reaction product is separated and purified to obtain the organic-inorganic hybrid material.
[0052] Specifically, the separation and purification methods are selected according to the product type. For PDMS-g-POSS hybrid materials, precipitation is used; for PFPE-g-POSS hybrid materials, filtration and column chromatography are used.
[0053] Furthermore, when the composition to be reacted contains polydimethylsiloxane, the catalyst is selected from at least one of boron trifluoride ether and triethylborane; when the composition to be reacted contains perfluoropolyether, the catalyst is selected from at least one of 4-dimethylaminopyridine and triethylamine.
[0054] Specifically, the catalyst is precisely matched with the type of flexible chain end group. When the composition to be reacted contains amino PDMS, the Lewis acid catalyst can activate the epoxy group, enhance its electrophilicity, and promote the nucleophilic ring-opening reaction of the amino group. When the composition to be reacted contains carboxyl PFPE, the tertiary amine catalyst (such as 4-dimethylaminopyridine) acts as a nucleophilic catalyst. Combined with the dehydrating agent DCC, it can efficiently promote the esterification ring-opening reaction of carboxyl and epoxy groups and avoid side reactions.
[0055] Further, the organic solvent is selected from at least one of toluene, tetrahydrofuran, and N,N-dimethylformamide; in step S1, if the composition to be reacted contains perfluoropolyether, a dehydrating agent is also added to the organic solvent, wherein the dehydrating agent is N,N-dicyclohexylcarbodiimide.
[0056] Specifically, organic solvents such as toluene, tetrahydrofuran, and N,N-dimethylformamide can be used. Toluene is suitable for the PDMS-g-POSS reaction; tetrahydrofuran is suitable for the PFPE-g-POSS reaction; and N,N-dimethylformamide is suitable for high-grafting-degree reactions. When the composition to be reacted contains carboxyl PFPE, adding the dehydrating agent DCC can remove the water generated in the reaction and improve the esterification efficiency.
[0057] In another embodiment of this application, a photocurable antifouling material is provided, comprising the above-mentioned organic-inorganic hybrid material and a photoinitiator.
[0058] In another embodiment of this application, an article is provided, the surface of which is coated with a coating formed by photocuring the aforementioned photocurable antifouling material.
[0059] The beneficial effects of this application will be further illustrated below with reference to the embodiments.
[0060] The present application will be further described in detail below with reference to the embodiments. All components described in the present application are obtained commercially available.
[0061] Example 1: Synthesis of PDMS-g-POSS-1 low-grafting-degree hybrid material
[0062] (1) Reaction apparatus and atmosphere control
[0063] In a 100mL three-necked flask equipped with a magnetic stirrer, a reflux condenser, and an inert gas (nitrogen) inlet / outlet port, high-purity nitrogen (≥99.99%) was introduced to replace the air in the system three times, maintaining a slightly positive nitrogen atmosphere (0.01-0.02MPa) to ensure that the reaction proceeds under anhydrous and oxygen-free conditions. This is to prevent O2 and H2O in the air from coordinating or hydrolyzing with the catalyst boron trifluoride diethyl ether compound (BF3·OEt2), thus ensuring catalyst activity and reaction selectivity.
[0064] (2) Raw material feeding and homogenization
[0065] Add the following ingredients to the three-necked flask in sequence:
[0066] Glycidyl etheroxypropyl cage-like polysilsesquioxane (Glycidyl POSS, purity ≥98%, 1.0g, containing approximately 1.35mmol of epoxy groups);
[0067] Single-terminated amino-terminated polydimethylsiloxane ( Number average molecular weight Mn≈1000g / mol, purity≥95%, 0.54g, 0.54mmol);
[0068] Anhydrous toluene (H2O content ≤10ppm, 10mL);
[0069] After the materials are added, turn on the magnetic stirrer and set the speed to 300-500 rpm. Stir for 15-20 minutes until all solids are completely dissolved to form a uniform and transparent reaction solution. This ensures that the reactant molecules are in full contact and avoids uneven grafting due to uneven local concentration.
[0070] (3) Targeted addition of catalyst
[0071] Under nitrogen protection, the Lewis acid catalyst boron trifluoride diethyl ether compound (BF3·OEt2, purity ≥99%, 0.02 mL) was slowly added dropwise using a 1 mL microsyringe at a dropping rate of 0.1 mL / min. BF3·OEt2, as a Lewis acid, can activate the epoxy three-membered ring and promote its nucleophilic ring-opening addition with the amino group. The slow dropwise addition can avoid the side reaction of epoxy self-polymerization caused by excessively high local catalyst concentration.
[0072] (4) Isothermal grafting reaction
[0073] The reaction system was heated to 80°C using an oil bath and stirred at this temperature for 24 hours. 80°C is the optimal reaction temperature for the ring-opening reaction of epoxy groups and amino groups, which can balance the reaction rate and the thermal stability of PDMS segments. The 24-hour reaction time can ensure that the epoxy group conversion rate is ≥90%.
[0074] (5) Precipitation separation
[0075] After the reaction is complete, the mixture is allowed to cool naturally to room temperature. Then, the reaction solution is slowly added dropwise to anhydrous methanol at 0-5℃ at a dropping rate of 0.5 mL / min. The amount of methanol used is 100 mL, which is 10 times the volume of the reaction solution. The mixture is stirred while being added, and a white flocculent precipitate is formed.
[0076] (6) Purification and drying
[0077] The precipitate was collected by vacuum filtration using a G3 sintered glass funnel and washed three times with 20 mL of anhydrous methanol at 0-5 °C to remove residual raw materials, catalyst, and solvent. The precipitate was then transferred to a vacuum drying oven and dried at 40 °C and a vacuum degree ≤ -0.095 MPa for 24 h to obtain a white powdery product PDMS-g-POSS-1, with a yield of approximately 85%.
[0078] (7) Structural characterization and grafting degree analysis
[0079] The structure of the product was confirmed by 1H NMR spectroscopy. The area of the epoxy group characteristic peak (δ≈2.5-2.8ppm, epoxy ring -CH-) of PDMS-g-POSS-1 was significantly reduced; and the characteristic peak of Si-CH3 of PDMS chain segment (δ≈0.1ppm) and the secondary hydroxyl peak formed by ring opening (δ≈3.5-4.0ppm, -CH(OH)-CH2-) appeared.
[0080] Grafting degree was calculated by integral ratio: using the POSS core-CH2-O- peak (δ≈3.2ppm) as an internal standard, the ratio of the reduction in epoxy peak area to the PDMSSi-CH3 peak area indicates that, on average, each POSS molecule is grafted with approximately 2 PDMS segments.
[0081] Example 2: Synthesis of PDMS-g-POSS-2 high-grafting-degree hybrid materials
[0082] The only difference between Example 2 and Example 1 is that the amount of single-amino-terminated polydimethylsiloxane used in Example 2 is 1.62g.
[0083] The reaction yielded the product PDMS-g-POSS-2. ¹H NMR analysis indicated that approximately four PDMS chains were grafted onto each POSS molecule on average.
[0084] Example 3: Synthesis of PFPE-g-POSS hybrid materials
[0085] (1) Reaction apparatus and atmosphere control
[0086] In a 100mL three-necked flask equipped with a magnetic stirrer, a reflux condenser, and a high-purity nitrogen (≥99.99%) inlet, nitrogen is introduced to replace the air in the system three times to maintain a slight positive pressure (0.01-0.02MPa) of nitrogen, ensuring an anhydrous and oxygen-free reaction environment and preventing moisture / oxygen in the air from causing epoxy group hydrolysis, carboxyl group oxidation, or interfering with catalyst activity.
[0087] (2) Raw material feeding and homogenization
[0088] Add the following ingredients to the flask in sequence:
[0089] Epoxycyclohexyl ethyl cage-like polysilsesquioxane (POSS, purity ≥98%, 1.2g);
[0090] Single-ended carboxyl-terminated perfluoropolyether (HOOC-PFPE, number average molecular weight Mn≈1500g / mol, purity ≥95%, 1.5g);
[0091] Anhydrous tetrahydrofuran (THF, water content ≤10ppm, 15mL);
[0092] After adding the materials, turn on the magnetic stirrer and set the speed to 300-500 rpm. Stir for 15 minutes until the solid is completely dissolved and a uniform and transparent reaction solution is formed.
[0093] (3) Addition of catalyst and dehydrating agent
[0094] The nucleophilic catalyst 4-dimethylaminopyridine (DMAP, purity ≥99%, 0.05g) and the dehydrating agent N,N-dicyclohexylcarbodiimide (DCC, purity ≥99%, 0.3g) were added. DMAP, as a tertiary amine catalyst, can activate the carbonyl group of the carboxyl group and promote its ring-opening addition reaction with the epoxy group. DCC, as a dehydrating agent, reacts with the carboxyl group to generate an active ester intermediate, thereby improving the reaction efficiency. At the same time, it captures the trace water generated in the reaction and inhibits side reactions.
[0095] (4) Isothermal grafting reaction
[0096] The reaction system was heated to 50°C using an oil bath and stirred for 36 hours. 50°C is the optimal reaction temperature for the carboxyl-epoxy ring-opening reaction, which can balance the reaction rate and the thermal stability of the PFPE chain segments. The 36-hour reaction time can ensure that the epoxy group conversion rate is ≥85%.
[0097] (5) Byproduct removal and solvent concentration
[0098] After the reaction was completed, the white precipitate of dicyclohexylurea (DCU) was removed by hot filtration using a G3 sintered glass funnel. DCU is a byproduct of DCC and is insoluble in THF, so filtration can remove it quickly. The filtrate was transferred to a rotary evaporator and evaporated under reduced pressure at 40°C and a vacuum of ≤-0.095MPa to remove more than 90% of the THF solvent. Low temperature and reduced pressure were used to avoid the volatilization or decomposition of PFPE segments.
[0099] (6) Column chromatography purification and product collection
[0100] 200-300 mesh silica gel was selected; ethyl acetate / petroleum ether was used as the eluent at a volume ratio of 1:4; the remaining concentrate was purified by silica gel column chromatography, and the product was separated from the unreacted raw material by utilizing the difference in polarity; the main fraction was collected, and the solvent was removed again by rotary evaporation under reduced pressure to obtain the colorless viscous liquid product PFPE-g-POSS, with a yield of about 70%.
[0101] (7) Structural characterization and verification
[0102] Fourier transform infrared (FTIR) spectroscopy: The product simultaneously exhibits the characteristic peak of CF stretching vibration of PFPE (~1200 cm⁻¹). -1 Characteristic peaks of the Si-O-Si framework of POSS (~1100 cm⁻¹) -1 Furthermore, the carboxyl carbonyl peak of the HOOC-PFPE raw material is approximately 1710 cm⁻¹.-1 The fact that the carboxyl group has almost completely disappeared proves that the carboxyl group has fully participated in the reaction.
[0103] 1H NMR: The characteristic peak of the POSS epoxy ring (δ≈2.6-3.0 ppm) is significantly weakened, and the characteristic peak of the secondary hydroxyl group formed by the ring-opening reaction (δ≈3.6-4.1 ppm) appears, along with the characteristic peak of the PFPE segment (δ≈1.0-1.5 ppm, terminal CH). 2- The grafting structure was confirmed to be successful.
[0104] Example 4: Preparation and Performance Testing of Photocurable Antifouling Coating
[0105] Step 1: Coating Preparation
[0106] Take 1.0 g of each of the hybrid materials synthesized in Example 1 (PDMS-g-POSS-1), Example 2 (PDMS-g-POSS-2), and Example 3 (PFPE-g-POSS), and add 3 wt% of triarylthionium salt and cationic photoinitiator IHT-PI 820 to each hybrid material to prepare a mixture.
[0107] The above mixtures were placed on magnetic stirrers and stirred at 300 rpm for 15 minutes until completely homogeneous to obtain photocurable resin liquid A (corresponding to PDMS-g-POSS-1), photocurable resin liquid B (corresponding to PDMS-g-POSS-2), and photocurable resin liquid C (corresponding to PFPE-g-POSS).
[0108] Step 2: Coating and Curing
[0109] (1) Substrate pretreatment: Clean the clean glass slide and tinplate with anhydrous ethanol for 10 minutes and dry them with nitrogen gas for later use.
[0110] (2) Coating: Use a #4 wire bar coater to evenly coat the resin liquid onto the surface of the pretreated substrate, and control the wet film thickness to be 50μm.
[0111] (3) Curing: The coated sample is placed in a UV curing machine and passed through the irradiation area at a conveying speed of 10m / min to complete the curing.
[0112] Step 3: Performance Testing
[0113] The cured coating was subjected to the following performance tests, each of which was repeated three times and the average value was taken:
[0114] (1) Transparency test: The transmittance of the coating in the visible light range of 400-800nm was measured using a UV-Vis spectrophotometer. The value at 550nm was taken. The test results are shown in Table 1.
[0115] (2) Adhesion test: According to GB / T 9286-1998 "Paints and Varnishes Cross-cut Test", a cross-cut tester with a 1mm spacing was used to cut a grid on the coating surface (cut through to the substrate). After peeling with 3M tape, the coating peeling was observed. The rating was 1 (the best). The test results are shown in Table 1.
[0116] (3) Pencil hardness test: According to GB / T 6739-2006 "Determination of paint film hardness by pencil method", Zhonghua brand pencil (hardness range 6B-9H) was used to scratch the coating surface at a 45° angle and a 1kg load. The highest pencil hardness that did not produce scratches was recorded. The test results are shown in Table 1.
[0117] (4) Initial water contact angle test: Using a contact angle measuring instrument, 5 μL of deionized water was added to the coating surface to test the static water contact angle. The average value of 5 different points was taken. The test results are shown in Table 1.
[0118] (5) Antifouling performance test after friction: Using a standard friction tester, the coating surface was rubbed back and forth 20 times with a 500g load and a rubber friction head (Shore A 60 hardness). The water contact angle of the friction area was tested again, and the retention rate was calculated. The test results are shown in Table 1.
[0119] (6) Abrasion resistance test: According to GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes by rotating rubber grinding wheel", the Taber abrasion tester was used with a CS-10 grinding wheel and the test was conducted under the conditions of 500g load and 500 revolutions. The mass loss of the coating was recorded. The test results are shown in Table 1.
[0120] Comparative Example 1: Pure epoxy-based POSS photocurable coating
[0121] Take 1.0g of unmodified Glycidyl POSS, add the same type and amount of photoinitiator, prepare a resin solution according to the same method as in Example 4, and coat and cure it. The test results are shown in Table 1.
[0122] Comparative Example 2: Physically blended coatings of POSS and PDMS
[0123] Take 0.7g of Glycidyl POSS and 0.3g of NH2-PDMS (Mn≈1000), add a photoinitiator, mix them directly without chemical reaction, and then coat and cure. The test results are shown in Table 1.
[0124] Table 1 shows the performance test results of the photocurable antifouling coatings prepared in Examples 1-3 and Comparative Examples 1-2:
[0125]
[0126] As shown in Table 1, the light transmittance of the photocurable antifouling coatings prepared using Examples 1-3 of this application is all >90%, with Example 1 at 92.5%, Example 2 at 91.8%, and Example 3 at 91.2%, and no hazing is observed. This indicates that the PDMS / PFPE flexible segments form a molecular-level dispersion system with the POSS inorganic core through chemical bonding, without macroscopic phase separation; the remaining epoxy groups participate in UV curing to form a uniform three-dimensional cross-linked network, avoiding micro-area scattering and ensuring high light transmittance. In contrast, although Comparative Example 2 uses POSS and PDMS, it uses physical blending, resulting in a light transmittance of only 81.3% and slight hazing. This shows that the unreacted PDMS has poor compatibility with POSS, forming micron-level phase-separated micro-regions that induce visible light scattering, leading to a significant decrease in transparency.
[0127] The photocurable antifouling coatings prepared using Examples 1-3 of this application all exhibited a pencil hardness ≥8H and a Taber wear loss of 1.5-2.1 mg. This demonstrates that the inorganic cage-like skeleton of POSS provides rigid support, while ungrafted epoxy groups participate in cross-linking to form a dense three-dimensional network. The flexible segments of PDMS / PFPE are anchored by chemical bonds, without compromising network integrity. Examples 1 and 2 show that a low grafting degree retains more epoxy groups, resulting in a higher cross-linking density and minimal wear loss. A high grafting degree increases the proportion of flexible chains, leading to a slight increase in wear loss, but it is still far superior to physical blending. Comparative Example 1, with a hardness of 9H and a wear loss of 1.2 mg, exhibits the best abrasion resistance but lacks antifouling properties. Comparative Example 2, with a hardness of only 5H and a wear loss of 8.4 mg, demonstrates that the photocurable antifouling coating of this application balances rigidity and flexibility, providing antifouling performance while maintaining high hardness and abrasion resistance, overcoming the limitations of pure POSS lacking antifouling properties and physical blending exhibiting poor mechanical properties.
[0128] Regarding antifouling performance, the initial water contact angles of the photocurable antifouling coatings prepared using Examples 1-3 of this application are all >100°, with the photocurable antifouling coating prepared in Example 3 (i.e., PFPE grafted) reaching 118°. This indicates that the low surface energy segments of PDMS / PFPE form a dynamic liquid-like layer on the coating surface, repelling water / oil / biological contaminants through the free movement of molecular chains, thus achieving high hydrophobicity. In contrast, Comparative Example 1 only achieved 78°, and Comparative Example 2 increased the initial water contact angle to 98° using PDMS. However, combined with other test indicators, this precisely demonstrates that the comprehensive improvement of POSS material performance cannot be achieved through simple physical blending.
[0129] Regarding durability and antifouling properties, the contact angle retention rates of the photocurable antifouling coatings prepared using Examples 1-3 of this application are all >97% after friction, indicating that the PDMS / PFPE segments are chemically anchored to the POSS crosslinking network and will not be stripped during friction; the dynamic segments continuously migrate to the surface, maintaining a low surface energy layer. In contrast, the retention rate of Comparative Example 2 is only 86.7%, indirectly indicating that the chemically anchored structure achieves durable antifouling and solves the problem of the lack of durability of traditional physical blend antifouling.
[0130] In summary, this application achieves a synergistic effect of high transparency, high hardness, wear resistance and durable antifouling performance through the structural innovation of chemical bond grafting of rigid POSS core and flexible antifouling chain segment. It breaks through the core contradiction of hardness and antifouling in traditional technology and provides a high-performance surface protection solution for optical devices, medical devices, marine facilities and other fields.
[0131] The various embodiments of this application have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. An organic-inorganic hybrid material for antifouling, characterized in that, The organic-inorganic hybrid material is prepared by a ring-opening addition reaction of the epoxy groups of epoxy polyhedral oligomeric silsesquioxane with amino groups or perfluoropolyether with carboxyl groups.
2. The organic-inorganic hybrid material for antifouling according to claim 1, characterized in that, The epoxy polyhedral oligomeric silsesquioxane is selected from at least one of glycidyl etheroxypropyl cage polysesquioxane and epoxycyclohexylethyl cage polysesquioxane.
3. The organic-inorganic hybrid material for antifouling according to claim 1, characterized in that, The polydimethylsiloxane has a number average molecular weight of 500–10000 g / mol and is selected from any one of mono-amino-terminated polydimethylsiloxane and di-amino-terminated polydimethylsiloxane; the perfluoropolyether has a number average molecular weight of 500–5000 g / mol and is selected from any one of mono-carboxyl-terminated perfluoropolyether and di-carboxyl-terminated perfluoropolyether.
4. The organic-inorganic hybrid material for antifouling according to claim 1, characterized in that, The number of polydimethylsiloxanes or perfluoropolyethers grafted onto each of the epoxy polyhedral oligomeric silsesquioxanes is 1 to 8.
5. A method for preparing an organic-inorganic hybrid material for antifouling as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Under inert gas protection and anhydrous conditions, epoxy polyhedral oligomeric silsesquioxane and catalyst are dissolved in an organic solvent, and then polydimethylsiloxane or perfluoropolyether dissolved in the organic solvent is added and mixed to obtain the composition to be reacted. S2. Stir the composition to be reacted at 50°C to 120°C for 4 to 48 hours to allow the epoxy group to undergo a ring-opening grafting reaction with the amino or carboxyl group; S3. After the reaction is completed, the reaction product is separated and purified to obtain the organic-inorganic hybrid material.
6. The method for preparing the organic-inorganic hybrid material for antifouling according to claim 5, characterized in that, When the composition to be reacted contains polydimethylsiloxane, the catalyst is selected from at least one of boron trifluoride diethyl ether and triethylborane; when the composition to be reacted contains perfluoropolyether, the catalyst is selected from at least one of 4-dimethylaminopyridine and triethylamine.
7. The method for preparing the organic-inorganic hybrid material for antifouling according to claim 6, characterized in that, The organic solvent is selected from at least one of toluene, tetrahydrofuran, and N,N-dimethylformamide; In step S1, if the composition to be reacted contains perfluoropolyether, a dehydrating agent, namely N,N-dicyclohexylcarbodiimide, needs to be added to the organic solvent.
8. A photocurable antifouling material, characterized in that, It includes the organic-inorganic hybrid material and photoinitiator as described in any one of claims 1 to 4.
9. The photocurable antifouling material according to claim 8, characterized in that, The photoinitiator is selected from at least one of cationic photoinitiators and free radical photoinitiators, and its amount is 0.5% to 5% of the mass of the organic-inorganic hybrid material.
10. An article characterized in that, The surface of the product is coated with a coating formed by photocuring the photocurable antifouling material of claim 8 or 9.
Citation Information
Cited By
High-branching-degree perfluoropolyether siloxane for high-performance anti-fingerprint coating as well as preparation method and application of high-branching-degree perfluoropolyether siloxane
CN121895585A